1986
DOI: 10.1002/actp.1986.010371108
|View full text |Cite
|
Sign up to set email alerts
|

Ultraschalluntersuchungen an Poly(propylenoxid) – Molekülmassenabhängigkeit und Lösungsmitteleinfluß

Abstract: An Poly(propylenoxid)proben verschiedener Molekülmassen (Mn = 500 bis 3500) wurden Ultraschallabsorptionsuntersuchungen in einem Frequenzbereich von 0,1 bis 100 MHz bei 20°C und 35°C durchgeführt. Darüber hinaus wurde an einigen Proben die dyanmische Scherviskosität im Frequenzbereich von 0,02 bis 90 MHz gemessen. Für Proben mit Molekülmassen über M ≈ 1300 wurde eine Veränderung des Charakters der Frequenzabhängigkeit sowohl für die effektive Viskosität als auch für die dynamische Scherviskosität beobachtet, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…However, PPO, because of its noncrystallizability and availability in a wide molecular weight range, is acceptable as a model object for close examination of relaxation properties of flexible chain polymers. Its relaxation characteristics, basically those of the corresponding low molecular weight OH-ended analogue, so-called poly(propylene glycol) (PPG), have been intensively studied using dielectric, [1][2][3][4][5][6] optical, 7-10 nuclear magnetic resonance (NMR), [11][12][13] quasi-elastic neutron scattering, 14,15 and ultrasonic, [16][17][18][19][20][21] techniques, as well as various methods for probing viscoelastic properties. [22][23][24] In contrast to PPO, PEO and PTMO are possible to crystallize and they can be closely investigated only in a temperature range above the melting point.…”
mentioning
confidence: 99%
“…However, PPO, because of its noncrystallizability and availability in a wide molecular weight range, is acceptable as a model object for close examination of relaxation properties of flexible chain polymers. Its relaxation characteristics, basically those of the corresponding low molecular weight OH-ended analogue, so-called poly(propylene glycol) (PPG), have been intensively studied using dielectric, [1][2][3][4][5][6] optical, 7-10 nuclear magnetic resonance (NMR), [11][12][13] quasi-elastic neutron scattering, 14,15 and ultrasonic, [16][17][18][19][20][21] techniques, as well as various methods for probing viscoelastic properties. [22][23][24] In contrast to PPO, PEO and PTMO are possible to crystallize and they can be closely investigated only in a temperature range above the melting point.…”
mentioning
confidence: 99%
“…Schonhal and Stauga37 studied the molecular dynamics of oligomeric PPG liquids ( M w = 1200, 2000 and 4000 g mol −1 ) confined porous glasses in using dielectric spectroscopy and confirmed that, in these molecules, besides the α‐relaxation there is the dynamics of a whole chain or of the larger part of it. Similarly Alig et al 38–41 studied the molecular dynamics of PPG of different molecular weights by ultrasonic spectroscopy, NMR, light scattering and theoretically, and concluded that hydrogen bonding causes a dynamic network to form in these molecules. Such a type of dynamic network (called ‘transient entanglements’ or temporary network) in PPG is due to the transient hydrogen‐bond structure of these molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was also confirmed that there are two‐dimensional and three‐dimensional structure growth in the PPG–PEG mixtures. According to the conformation of PPG molecules,38–41 Steinhoff et al 42 assumed a transient hydrogen‐bond structure for blends of two poly glycols. In contrast to the conformation of PPG–PEG mixtures by phase separation study, we can also assume that different complex interactions will occur when the dynamic network of PPG is mixed with varying molecular weight flexible PEG molecules in their pure liquid state for the preparation of dilute solutions in non‐polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonds were measured by infrared spectroscopy in PEG 43 and PPG. 44,45 For PPG, ultrasound absorption 46 and nuclear magnetic resonance measurements 47 showed an additional low frequency relaxation process with characteristics typical for entanglement effects. The process occurred in samples with molar masses M n > 1300 g mol À1 , far below the critical molar mass of PPG for entanglements (M C % 7000 g mol…”
Section: A Phase Diagrammentioning
confidence: 99%